Slow(ed) Scholarship: On Crip Time and Refusal from the Intersections of Privilege and Precarity - Kaufman, E.C.; Chennault, Carrie; Molana, Hanieh (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This roundtable tells a story of three early career feminist critical geographers, facing disabling conditions and the pressures of neoliberal time in academia. Our introductory essay reviews the rich literature on slow scholarship, crip time, disabilities, and neurodivergence that resonated with us. We connect these themes with our personal journeys navigating crip time and refusal in North American academic institutions through a recorded roundtable discussion, transcribed below. In rethinking what slowing down and refusal mean from the perspective of an already slowed bodymind, we hope that this article stimulates more conversations among critical scholars at all stages of their careers. Aspects of the roundtable will be relatable to those facing varying levels of precarity, neurodivergence, and disabling conditions. With compassion for embodied barriers and time pressures we also encourage tenured and variously more secure and well-established scholars to read this piece and consider ways to alter the material conditions of inequity, stress, and mental and physical pain experienced by scholars at the intersections we describe. A commitment to slow scholarship in feminist and critical geographies, we contend, demands a commitment to those who wrestle with time and disability in academia, and to those who inhabit the paradox between slowing down and keeping up.